Efeito do tratamento térmico de revenimento na fragilização pelo hidrogênio do aço 9% Ni em água do mar sintética e tiossulfato de sódio - Gama, Gama (2018)
The use and adequacy of metallic alloys to attend the design requirements for the new oil production and exploration scenarios in Brazilian fields promotes a daily challenge for industries, professionals and research centres to guarantee the quality and safety of emerging business. The large amount of CO2 gas the PreSalt wells allows the reinjection of the gas to increase the recovery factor and the productivity. In this sense, 9% Ni steels becomes a technological alternative for application in CO2 injection systems due to the high toughness presented at cryogenic temperatures. However, the behaviour of this material in environments containing wet CO2 / H2S must be studied for a better understanding and establishment of their applicability limitations. This paper presents an evaluation about the tempering heat treatment influence on the hydrogen embrittlement of 9% Ni steel in synthetic seawater and sodium thiosulfate (Na2S2O3). The Slow Strain Rate Test (SSRT) results showed the effect of the environment in the toughness, elongation and rupture time in comparison with the result in the air at the same deformation rate, evidencing the embrittlement process of the 9% Ni steel. These tests, associated with microstructural and fracture mechanisms characterization complement the results and conclusions presented on this research.